(untitled) (Baghdad Science Journal, 2024)
A series of Mefenamic acid derivatives were designed and synthesized and the products were characterized spectroscopically using FT-IR, 1H NMR, and 13C NMR techniques. Series A included the transformation of six drugs (Mefenamic acid, Ampiciline, Noproxen, Benzilic acid, Diclofenac acid, and cephics) which are known to have highly medicinal effectiveness to acid chloride then react with thiosemicarbazide to synthesize series B. In the third stage, oxadiazole was prepared using POCl3 as a ring-closing agent to compounds (B1-B6). The final step in the strategy was building new Mefenamic acid derivatives consisting of condensation of the Mefenamic acid chloride with the compounds (C1-C6) to give new compounds (D1-D6).